A Postphenomenological Framework for Studying User Experience of Immersive Virtual Reality - Vindenes, Joakim; Wasson, Barbara (Frontiers in Virtual Reality, 2021)
Virtual Reality (VR) is a remarkably flexible technology for interventions as it allows the construction of virtual worlds with ontologies radically different from the real world. By embodying users in avatars situated in these virtual environments, researchers can effectively intervene and instil positive change in the form of therapy or education, as well as affect a variety of cognitive changes. Due to the capabilities of VR to mediate both the environments in which we are immersed, as well as our situated relation towards those environments, VR has become a powerful technology for “changing the self.” As the virtually mediated experience is what renders these interventions effective, frameworks are needed for describing and analysing the mediations brought by various virtual world designs. As a step towards a broader understanding of how VR mediates experience, we propose a postphenomenological framework for conducting studies on VR mediation. Postphenomenology is a philosophy of technology concerned with empirical data that understand technologies as mediators of human-world relationships. Drawing on postphenomenological theory, our framework presents considerations for VR researchers wanting to approach user experience in VR from a mediation perspective. By addressing how mediations occur within VR as a user-environment relation and outside VR as a human-world relation, the framework addresses the various constituents of the virtually mediated experience. We demonstrate the framework's applicability by presenting the results of an analysis of a selected variety of studies that intend various user-environment relations to mediate various human-world relations.